Sépultures privilégiées dans la cité des Pictons : l’espace funéraire de Jaunay-Clan (Vienne) - Maxence Segard; Rémi Corbineau; Cécile de Seréville-Niel; Antoinette Rast-Eicher (Gallia)
A rescue excavation undertaken in 2011-2012 in Jaunay-Clan (Vienne) revealed a Late Antique funerary area consisting of a pyre, a mausoleum and a large masonry building. The pyre yielded significant accompanying goods, and is associated with a large deposit of broken vases. The surrounding enclosure and the stone pedestal undoubtedly correspond to the final construction of the burial. In the mausoleum, the embalming of bodies and the use of precious textiles (some of which are dyed Tyrian purple) provide evidence of elite funerary practices in the Pictons civitas in the 3rd-4th c. AD.